Marketing Strategy and Product Quality to Improve Purchase Intention at Lastry Bakery Tuban - Widyaningrum, Santi; Sudarmiatin , Sudarmiatin; Rahayu , Wening Patmi (Journal of Finance and Business Digital, 2024)
This research aims to analyze marketing strategies and product quality as important factors to improve purchase intention at Bu Lastry Bakery Bakery, one of MSME’s  located in Kerek District, Tuban, East Java, Indonesia. This research uses qualitative research methods with the sample used being interviews with the owner of the Bu Lastry Bakery. The results of this research show that effective marketing strategies such as creative advertising and consistent product quality can significantly improve purchase intention. The conclusion of this research is to provide insight to the management of Bu Lastry Bakery to optimize marketing strategies, improve product quality and strengthen its position amidst intense competition. It is hoped that the results of this research can contribute to the development of more effective marketing strategies in the bakery industry and other business sectors.